2021
DOI: 10.3390/cancers13102485
|View full text |Cite
|
Sign up to set email alerts
|

HCV Proteins Modulate the Host Cell miRNA Expression Contributing to Hepatitis C Pathogenesis and Hepatocellular Carcinoma Development

Abstract: Hepatitis C virus (HCV) genome encodes for one long polyprotein that is processed by cellular and viral proteases to generate 10 polypeptides. The viral structural proteins include the core protein, and the envelope glycoproteins E1 and E2, present at the surface of HCV particles. Non-structural (NS) proteins consist of NS1, NS2, NS3, NS4A, NS4B, NS5a, and NS5b and have a variable function in HCV RNA replication and particle assembly. Recent findings evidenced the capacity of HCV virus to modulate host cell fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 166 publications
(220 reference statements)
0
14
0
Order By: Relevance
“…The mechanisms that drive liver injury during HCV infection have not been fully elucidated. Several studies have attempted to understand the interactions between viral proteins and the cellular host machinery[ 93 ]. An important effort has been made to address and understand the complex interconnections between HCV infection and miRNAs, aimed at finding new therapeutic and diagnostic tools.…”
Section: Hcv-related Hcc Mirna-based Approachesmentioning
confidence: 99%
“…The mechanisms that drive liver injury during HCV infection have not been fully elucidated. Several studies have attempted to understand the interactions between viral proteins and the cellular host machinery[ 93 ]. An important effort has been made to address and understand the complex interconnections between HCV infection and miRNAs, aimed at finding new therapeutic and diagnostic tools.…”
Section: Hcv-related Hcc Mirna-based Approachesmentioning
confidence: 99%
“…Dysregulation induced by HCV involves also miRNAs [ 48 ]. In vitro studies showed that core and NS4B proteins can independently activate miR-27a and miR-27b expression, promoting lipogenesis and subsequently steatosis.…”
Section: Molecular Mechanism Of Hcc Development In Hcv Patientsmentioning
confidence: 99%
“…HCV does not seem to encode viral microRNA probably because of its cytoplasmic location, which deprives the virus from nuclear proteins, such as RNA polymerase II and Drosha, required for microRNA biogenesis. However, comparative microRNAome profiling of HBV-associated HCCs and HBV-negative HCCs, and of HepG2 hepatocytes stably transfected and full-length HCV genome and control cells demonstrated that HCV elicited changes in cellular miRNA expression [ 238 , 261 , 262 , 263 ]. MicroRNAs including miR-30c, miR-122, miR-124, miR-138, miR-152, and miR-203 were downregulated, whereas miR-21, miR-93, 193b, miR-196a, and miR-758 were upregulated.…”
Section: Oncoviruses and Micrornamentioning
confidence: 99%
“…Another mechanism by which the core protein affected microRNA levels was by suppressing the activity of Dicer, thereby interfering with the biogenesis of microRNAs [ 264 ]. The non-structural proteins NS3, NS4A, NS4B, and NS5A also affected the expression of cellular microRNAs that stimulate proliferation, cell survival, migration and invasion, and immune evasion [ 238 ]. The mechanisms by which these HCV proteins modify microRNA expression remains to be determined.…”
Section: Oncoviruses and Micrornamentioning
confidence: 99%